The Thoughts And Struggles Of Dr Burhanuddin Al Helmy - Ishak Saat, Mohd Kasri Saidon, Ahmad Zainudin Husin, Khairi Ariffin (International Journal of Advanced Science and Technology, 2020)
This article discusses on the thoughts and struggle pioneered by Dr Burhanuddin Al-Helmy. An Islamic nationalist and a fighter who loved his country and who struggled for the independence of Malaya. Dr Burhanuddin Al-Helmy had chosen the rule of law in his political approach. This is proven during the time he led the Malay Nationalist Party (MNP), Pusat Tenaga Rakyat (PUTERA) and Pan Malaysian Islamic Party (PAS). This article is about a biographical study. With reference to the primary and secondary sources to analyse the thoughts and struggle led by Dr Burhanuddin Al-Helmy. In fact, this study also aims to clarify his thoughts and translate them through his political struggle. As such, he often faced various challenges in the political struggle. The study concludes that his thinking and struggle were accepted by the young Malay generation who loved their country, Malaya and who worked together for the independence of Malaya.